1993
DOI: 10.7326/0003-4819-119-1-199307010-00006
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Lower Extremity Clinical Abnormalities in Patients with Non-Insulin-Dependent Diabetes Mellitus

Abstract: An intervention designed to reduce risk factors for lower extremity amputations positively affected patient self-foot-care behavior as well as the foot care given by health care providers and reduced the prevalence of lower extremity clinical disease in patients with diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
238
1
9

Year Published

1995
1995
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 358 publications
(257 citation statements)
references
References 0 publications
9
238
1
9
Order By: Relevance
“…Foot-care education is widely recommended for persons with diabetes [11][12][13]20], and items related to foot care have been included in surveys of diabetes selfmanagement [23]. However, no validated, widely accepted instruments have been dedicated to the assessment of foot-care quality, related professional foot services, or resulting foot self-care practices.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Foot-care education is widely recommended for persons with diabetes [11][12][13]20], and items related to foot care have been included in surveys of diabetes selfmanagement [23]. However, no validated, widely accepted instruments have been dedicated to the assessment of foot-care quality, related professional foot services, or resulting foot self-care practices.…”
Section: Discussionmentioning
confidence: 99%
“…Recommended self-care practices include regular inspection of feet, selection of appropriate footwear, and avoidance of risks such as sharp instruments and abrasives [11][12]. Well-coordinated preventive foot care can reduce diabetes-related lower-limb complications [13][14][15]. Consensus on methods of care for the diabetic foot is emerging internationally, and cost-effectiveness projections indicate that guideline-based treatment for diabetic foot problems may improve clinical outcomes and decrease total costs [16].…”
Section: Introductionmentioning
confidence: 99%
“…Anderson, Wolf, Burkhart, Cornell, & Bacon, 1989;Delamater et al, 1991;Litzelman et al, 1993). More recent studies have focused on adapting cognitive-behavioral therapies (CBT) for diabetic populations.…”
Section: Individual Characteristicsmentioning
confidence: 99%
“…86,87 Each of the studies used a comprehensive program of diagnosis (including monofilament testing) and intervention. Both trials showed a significant reduction in FIGURE 2.…”
Section: Neuropathy and Foot Carementioning
confidence: 99%